Radon fluxes at four uranium mill tailings disposal sites after about 20 years of service. (October 2021) - Fuhrmann, Mark; Benson, Craig H.; Likos, William J.; Stefani, Nicolas; Michaud, Alex; Waugh, W. Joseph; Williams, Morgan M.
Abstract: To evaluate the properties of earthen covers over uranium mill tailings disposal cells after about 20 years of service, we measured Rn-222 fluxes and radon barrier properties at the Falls City, TX, Bluewater, NM, Shirley Basin South, WY, and Lakeview, OR disposal sites in western USA. A total of 115 in-service Rn fluxes were obtained at 26 test pit locations from the top surface of the exposed Rn barrier (i.e., after protective layers were removed by excavation) and 24 measurements were obtained from the surface of the underlying waste after excavation through the Rn barrier layer. Rn-222 concentrations were determined in accumulation chambers using a continuously monitoring electronic radon monitor (ERM) equipped with a solid-state alpha particle detector. Effects of surface features on Rn flux including vegetation, seasonal ponding, and animal burrowing were quantified. Comparison of measured fluxes with values that were measured shortly after the Rn barriers were completed (as-built) show that most measurements fell within the range of the as-built fluxes, generally at very low fluxes. At two sites fluxes were measured that were greater than the highest as-built flux. High fluxes are typically caused by a combination of enhanced moisture removal and preferential pathways for Rn transport, often caused by deep-rooted plants. Such localized features result in a spatially heterogeneous distribution of fluxes that can vary substantially over only a meter or two. Highlights: Rn fluxes were measured at 4 U mill tailing disposal sites after about 20 years of service. Fluxes at all sites were acceptable but increasing at some sites. Fluxes at large woody plants were quantified and compared to control locations. Rn fluxes were patchy, sometimes with 10-fold differences over about a meter.